2009
DOI: 10.1016/j.otohns.2009.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive video‐assisted thyroidectomy: A retrospective study over two years of experience

Abstract: We found statistically improved operative times, hospital stay, and blood loss the first 2 years with a low rate of temporary complications. It appears that minimally invasive video-assisted thyroidectomy is a safe and feasible option to standard thyroidectomy in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…13,14 Total laparoscopic thyroidectomy and cholecystectomy have since become widely performed in many medical centres, and the concept of a minimally invasive, aesthetic procedure has been accepted by many surgeons and welcomed by patients. 15,16 Improvements in laparoscopic technology and instruments have resulted in more surgeons being willing to attempt this approach. 17,18 New instrumentation and strategies have alleviated some of the challenges of performing laparoscopy through a single abdominal incision for a range of gynaecological procedures.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Total laparoscopic thyroidectomy and cholecystectomy have since become widely performed in many medical centres, and the concept of a minimally invasive, aesthetic procedure has been accepted by many surgeons and welcomed by patients. 15,16 Improvements in laparoscopic technology and instruments have resulted in more surgeons being willing to attempt this approach. 17,18 New instrumentation and strategies have alleviated some of the challenges of performing laparoscopy through a single abdominal incision for a range of gynaecological procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its reduced surgical injury, better wound healing and better cosmetic outcome, this new technique has been widely applied in the treatment of thyroid carcinoma and made exciting outcomes (32)(33)(34)(35). Although the video-assisted surgical technique has much experience in thyroidectomy and central neck lymphadenectomy (5,10,13,15,33,36), its application in lateral neck lymph node dissection has been little reported. Several reports have presented the example of successful lateral neck lymphadenectomy using robotic surgical technique (6,16,37,38), but its application has been limited due to the high cost and the special request for the surgical equipment.…”
Section: Discussionmentioning
confidence: 99%
“…In the early years, only a few reports were issued in journals (Navarra et al, 1997) and most surgeons did not think such a "difficult" operation, other than providing scar reduction, would be beneficial for patients. In recent years, after scarless endoscopic thyroidectomy was widely performed in many medical centers, the concept of a minimally invasive esthetic operation had been accepted by many surgeons, because it was welcomed by many patients (Snissarenko et al, 2009). More surgeons found that TSPLC was not as difficult as before with the development of laparoscopic technology and instrument upgrades (Romanelli et al, 2008;.…”
Section: Discussionmentioning
confidence: 99%